Curiosity did not kill the cat: It made it stronger and happy, but only if the cat was not “dark” - Junça Silva, A.; Silva, D. (Acta Psychologica, 2021)
Objective The present research explores the path between work-related curiosity and positive affect. To justify this relationship, we rely on the conservation of resources theory (COR) and include performance as a mediator of the curiosity-positive affect path, such that curiosity was expected to stimulate performance, resulting in higher positive affect. We also aimed to explore whether the Dark Triad personality would moderate this mediating path. Methodology Three studies were conducted. Study 1 analyzed the indirect path of curiosity on positive affect through performance (n = 241). Study 2 resorted to two samples, one with participants in telework (n = 406), and the other one with participants in face-to-face work (n = 240), to explore the mediated link. Study 3 (n = 653) explored the moderating role of the Dark Triad traits (Machiavellianism, psychopathy, and narcissism) on the mediated relationship. Findings Study 1 demonstrated that curiosity boosted positive affect through performance. Study 2 showed that, when workers were in telework, the mediated relationship occurred, however the same did not happen in face-to-face work. Study 3 showed that Machiavellianism and psychopathy moderated the indirect effect of curiosity on positive affect through performance, in a way that it was present for individuals low on these traits, but not for individuals high on such traits. Narcissism did not moderate the mediated relationship. Implications We discuss the impact that curiosity may have on behavioral and affective consequences (performance and affect), and the role that personality may have on this relationship.